Effectiveness and Safety of Intramyocardial Needle Ablation for Refractory Ventricular Tachycardia and Premature Ventricular Complexes: A Systematic Review and Meta‐Analysis. - Gupta, Kartik; Qureshi, Muhammad Ahmad; Rawlley, Bharat; Jain, Vardhmaan; Verma, Atul; Siontis, Konstantinos C.; Deskhmukh, Abhishekh; Khan, Arfaat; Raad, Mohamad (Journal of Cardiovascular Electrophysiology, 2025)
Introduction: Intramyocardial needle ablation is a novel technique for treating refractory ventricular tachycardia (VT) and premature ventricular complexes (PVC). However, studies defining the effectiveness and safety of this procedure are limited. This meta‐analysis aims to evaluate the safety and effectiveness of needle ablation for VT and PVC refractory to standard ablation. Methods: Embase, Ovid (includes Medline), and ClinicalTrials.gov were searched from inception to December 31, 2024. Human studies on needle ablation for recurrent VT and PVC were included. Primary outcome was immediate effectiveness (no immediate post‐procedural inducible VT or PVC). Secondary outcomes were long‐term effectiveness (no clinical VT or PVC at 6 months) and safety (composite measure of peri‐ and post‐procedural complications). Results: A total of five studies including 180 patients (140 VT; 40 PVC) were analyzed. Mean ages ranged from 54 to 66 years. Among 129 patients with VT, immediate effectiveness was 75% (95% CI, 54–92; I2 80%), and cumulative freedom from clinical VT dropped to 43% at 6 months (95% CI, 35–52; I2 0%). Among 40 patients with PVC, immediate effectiveness was 82% (95% CI, 67–94; I2 0%), and long‐term effectiveness was 76% (95% CI, 61–90; I2 0%). Safety outcomes were reported in 19% of patients (95% CI, 13–27; I2 0%) and 10% of patients (95% CI 1, 23; I2 0%) in the VT and PVC arm, respectively. Death related to ablation was report in 7 patients (5.0%) only in the VT studies. Conclusion: Intramyocardial needle ablation is an emerging alternative approach for refractory VT and PVC ablation, showing cautious but promising results and safety profiles. Prospective studies and an international registry could provide valuable insights needed for optimal patient selection and protocol refinement.